2018
DOI: 10.1002/aah.10018
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Achlya oblongata Infection in Freshwater‐Reared Asian Seabass Lates calcarifer

Abstract: In September 2014, a freshwater oomycete was first isolated from Asian Seabass Lates calcarifer fry that were reared in freshwater at a fish hatchery in Sabah, Malaysia. A fungal strain was isolated from infected fry by using glucose yeast extract (GY) agar. From morphological identification, the strain belonged to the genus Achlya based on the mode of zoospore release. Molecular phylogenetic analysis of the internal transcribed spacer region sequences from the strain showed high similarity (99-100%) to Achlya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…FIRST REPORT OF ACHLYA BISEXUALIS IN SOUTH AFRICA 359 cotton, wool-like appearance of mycelia covering dermal erosions or skin lesions (Chukanhom and Hatai 2004;Andrew et al 2008;Refai et al 2016;Lau et al 2018). The infectious agent from this study showed similar clinical signs, with superficial, cotton, wool-like mycelia covering the eye of an Orange Blotched Peacock Cichlid.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…FIRST REPORT OF ACHLYA BISEXUALIS IN SOUTH AFRICA 359 cotton, wool-like appearance of mycelia covering dermal erosions or skin lesions (Chukanhom and Hatai 2004;Andrew et al 2008;Refai et al 2016;Lau et al 2018). The infectious agent from this study showed similar clinical signs, with superficial, cotton, wool-like mycelia covering the eye of an Orange Blotched Peacock Cichlid.…”
Section: Discussionsupporting
confidence: 57%
“…Achlya spp. have been confirmed as pathogenic agents causing mycoses in aquaculture, specifically in tropical environments where infection has been reported to affect economically important cultured fish species (Lawhavinit et al 2002;Webster and Weber 2007;Lau et al 2018). Infections with Achlya spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations